HISBAH: LEMBAGA KEAMANAN HUKUM DAN PERADILAN - Kamsi, Kamsi (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
H}isbah is an important way of monitoring is known by the Muslims in the early days of Islam that completes supervision to correct and prevent ethical lapses. H}isbah during Umar have an important role in market surveillance and the activities carried out in them, which is ekonomi. This article is aimed at the most important things that exist in the economy by Umar jurisprudence on h}isbah and its role in overseeing economic activities. H}isbah is in etimolgy and terminology revolves around the ordering good and forbidding the evil (amar ma’ruf nahi munkar). Terminological meaning h}isbah was ordered to leave if there is goodness and forbid unjust if there are practiced. The concept of hisbah above extends to cover all members of society capable of ordering the good and forbidding the evil, whether they are assigned by the state or did not required by resmi. Sebagaimana space h}isbah scope includes the rights of Allah and the rights of man. This means that h}isbah cover all facets of life. Where is the discussion here will be narrowed explanation h}isbah implementation by the state at the time of Umar in matters related to the economy